Analisis Pengelolaan Pajak Daerah dalam Meningkatkan Pendapatan Asli Daerah di Kabupaten Supiori - Irsat, Irsat; Haz, Musdalifah; Ruland Paskah Rumasew (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
Local taxes are one of the main components of PAD which have a strategic role in realizing fiscal independence and supporting regional development. This study aims to analyze tax management in an effort to increase Local Original Income in Supiori Regency. The study was conducted at the Regional Revenue Agency of Supiori Regency, related to the management of local taxes in Supiori Regency. The type of research that will be used in this study is a qualitative descriptive research type. Data collection techniques are carried out through observation, interviews, and documentation studies. The results of the study indicate that the main challenges in managing local taxes in Supiori Regency include low taxpayer awareness, minimal socialization, the absence of supporting regulations, technical obstacles in the field during collection, and limited budget support.